LEGAL STATUS OF PRECAUTIONARY PRINCIPLE IN ENVIRONMENTAL JURISPRUDENCE (NATIONAL CAPITAL LAW JOURNAL, 2000)
NA
Keywords: Precautionary Principle; Environmental Jurisprudence; Sustainable Development; Environmental Impact Assessment; Environmental Audit; Assimilative Capacity Principle; Scientific Uncertainty; Customary International Law; Burden Of Proof; Environmental Protection